Cognitive Reappraisal Facilitates Decentering: A Longitudinal Cross-Lagged Analysis Study - Kobayashi, Ryota; Shigematsu, Jun; Miyatani, Makoto; Nakao, Takashi (Frontiers in Psychology, 2020)
Previous studies have suggested that cognitive reappraisal, which is an effective emotion regulation strategy, enhances decentering. On the other hand, other studies have implied the reverse in regard to this relationship: that decentering supports cognitive reappraisal. However, these possibilities have not yet been examined empirically. In the present study, we investigated the causal relationship between decentering and cognitive reappraisal by conducting two wave cross-lagged analysis. One hundred and thirty-eight Japanese university students responded to a questionnaire comprising measures of decentering and cognitive reappraisal tendency; the questionnaire was administered on two occasions, with an interval of one month. Cross-lagged analysis indicated the positive effect of cognitive reappraisal on decentering; however, the reverse possibility, that decentering influences cognitive reappraisal, was not significant. These results suggested that habitual use of cognitive reappraisal fosters decentering.